Plastid Genome Evolution in the Early-Diverging Legume Subfamily Cercidoideae (Fabaceae) - Wang, Yin-Huan; Wicke, Susann; Wang, Hong; Jin, Jian-Jun; Chen, Si-Yun; Zhang, Shu-Dong; Li, De-Zhu; Yi, Ting-Shuang (Frontiers in plant science, 2018)
The subfamily Cercidoideae is an early-branching legume lineage, which consists of 13 genera distributed in the tropical and warm temperate Northern Hemisphere. A previous study detected two plastid genomic variations in this subfamily, but the limited taxon sampling left the overall plastid genome (plastome) diversification across the subfamily unaddressed, and phylogenetic relationships within this clade remained unresolved. Here, we assembled eight plastomes from seven Cercidoideae genera and conducted phylogenomic-comparative analyses in a broad evolutionary framework across legumes. The plastomes of Cercidoideae all exhibited a typical quadripartite structure with a conserved gene content typical of most angiosperm plastomes. Plastome size ranged from 151,705 to 165,416 bp, mainly due to the expansion and contraction of inverted repeat (IR) regions. The order of genes varied due to the occurrence of several inversions. In species, a plastome with a 29-bp IR-mediated inversion was found to coexist with a canonical-type plastome, and the abundance of the two arrangements of isomeric molecules differed between individuals. Complete plastome data were much more efficient at resolving intergeneric relationships of Cercidoideae than the previously used selection of only a few plastid or nuclear loci. In sum, our study revealed novel insights into the structural diversification of plastomes in an early-branching legume lineage, and, thus, into the evolutionary trajectories of legume plastomes in general.